Surgical Treatment of Decompensated Cicatricial Stricture of the Esophagus, Grade III-IV Dysphagia, and Compression Syndrome Caused by Nontoxic Multinodular Goiter: A Case Report - I. N. Danilov; A. A. Kovalev; A. V. Starzhevskaya; M. A. Salov; D. B. Nasedkin; E. G. Solonitsyn; A. S. Shulyakovskaya; A. E. Neimark (Инновационная медицина Кубани)
Objective: Long-standing gastroesophageal reflux disease is the most common cause of a cicatricial stricture of the esophagus. The treatment of this pathology involves a wide range of methods including conservative and surgical options. Surgeons can encounter technical difficulties in case of concomitant neck and chest pathology.Clinical case: We report a case of a decompensated cicatricial stricture of the esophagus with concomitant paraesophageal hiatal hernia, refractory gastroesophageal reflux disease, and nontoxic multinodular goiter (166.9 cm3). Selecting the optimal management for such patients is often a challenge. Staged treatment significantly improves postoperative quality of life, but the increased length of hospital stay can negatively impact patient compliance.